2013
DOI: 10.1590/s1516-35982013000500002
|View full text |Cite
|
Sign up to set email alerts
|

Forage accumulation in brachiaria grass under continuous grazing with single or variable height during the seasons of the year

Abstract: -The objective of this study was to evaluate grazing management strategies of Brachiaria decumbens cv. Basilisk managed with different heights under continuous grazing with cattle. Two grazing management strategies were evaluated: maintenance of pasture with an average height of 25 cm throughout the experimental period and maintenance of pasture on the average of 15 cm in height during winter, up to 25 cm from the beginning of spring. The split-plot scheme and the randomized block design with four replications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
8
1
1
Order By: Relevance
“…In this regard, in order to optimise forage accumulation in palisadegrass, the current recommendation is to maintain pastures under a continuous stocking rate, at a height of 20 to 40 cm (DA SILVA et al, 2013). However, one hypothesis is that the sward height should be flexible throughout the year (SANTOS; FONSECA; GOMES, 2013;PESSOA et al, 2016). Increasing the height from winter to summer would increase plant growth and minimise the elongation of the stem compared with maintaining the sward at a constant height.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in order to optimise forage accumulation in palisadegrass, the current recommendation is to maintain pastures under a continuous stocking rate, at a height of 20 to 40 cm (DA SILVA et al, 2013). However, one hypothesis is that the sward height should be flexible throughout the year (SANTOS; FONSECA; GOMES, 2013;PESSOA et al, 2016). Increasing the height from winter to summer would increase plant growth and minimise the elongation of the stem compared with maintaining the sward at a constant height.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, average pasture height has been recommended as a management criterion for when to commence and cease grazing (Silva and Nascimento Júnior 2007). Studies on grazing management strategies, based on pasture height, enable the understanding of variations in pasture structure, as well as the responses of animals and plants to these variations (Trindade et al 2007;Fonseca et al 2012Fonseca et al , 2013. Sbrissia et al (2010) suggested that the optimal height range for management of marandu palisadegrass (Urochloa brizantha syn.…”
Section: Introductionmentioning
confidence: 99%
“…Marandu) under continuous grazing during the rainy season was 20-40 cm. However, Santos et al (2013) suggested that pasture height should be adjusted according to the season of the year to optimize the productivity of the pasture. Other studies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this research aimed at assessing quantitative and qualitative carcass characteristics in purebred Nellore and crossbred Nellore x Santa Gertrudis cows reared exclusively on brachiaria pastures (Brachiaria decumbens and Brachiaria brizantha cv. Marandu), once these grass species cover more than 80% of Brazilian grazing areas (SANTOS et al, 2013). Thirty-two female bovines of around 32 ± 1.5 months of age, being 16 purebred Nellore and 16 crossbred Nellore and Santa Gertrudis.…”
Section: Introductionmentioning
confidence: 99%